Markups in Canada: Have they changed and why? - Danny Leung (Bank of Canada, 2008)
Many empirical studies have examined the cyclical nature of the markup ratio. Until recently, few have attempted to ascertain the changes in the markup over a longer time horizon. These changes are of no less interest in view of the posited effects of increasing import competition and lower inflation on the markup. This paper offers evidence on the evolution of the markups for the Canadian business sector and 33 disaggregate industries over the 19612004 period. It is found that the business sector markup has declined since the mid-1980s, and that import competition has made a statistically significant but small contribution to this decline.
Keywords: E31; F41; L11; 330; Econometric and statistical methods; Betriebliche Preispolitik; Handelsspanne; Import; Wettbewerb; Inflation Targeting; Verarbeitendes Gewerbe; Kanada